Walk 11 AT A GROVE - -, - (project baikal, 2012)
Zvezdochka Grove Lomonosov School in Irkutsk St Vladimir School The Residential Complex “Zavidnyi” “Mebel.RU” Store on Gogol Street School № 80 on Pushkin Street